Unsettling Translation Studies in Honour of Theo Hermans - Baker, Mona (Taylor & Francis, 2022)
This collection engages with translation and interpreting from a diverse but complementary range of perspectives, in dialogue with the seminal work of Theo Hermans. A foundational figure in the field, Hermans's scholarly engagement with translation spans several key areas, including history of translation, metaphor, norms, ethics, ideology, methodology, and the critical reconceptualization of the positioning of the translator and of translation itself as a social and hermeneutic practice. Those he has mentored or inspired through his lectures and pioneering publications over the years are now household names in the field, with many represented in this volume. They come together here both to critically re-examine translation as a social, political and conceptual site of negotiation and to celebrate his contributions to the field. The volume opens with an extended introduction and personal tribute by the editor, which situates Hermans's work within the broader development of critical thinking about translation from the 1970s onward. This is followed by five parts, each addressing a theme that has been broadly taken up by Theo Hermans in his own work: translational epistemologies; historicizing translation; performing translation; centres and peripheries; and digital encounters. This is important reading for translation scholars, researchers and advanced students on courses covering key trends and theories in translation studies, and those engaging with the history of the discipline.